Tourism sites naming in Ciletuh geopark: Toponymic and morphological studies - Sujatna, Eva Tuckyta Sari; Pamungkas, Kasno; Heriyanto (Kasetsart Journal of Social Sciences, 2021)
This article attempts to show the correlation of tourism sites naming to Toponymy and Morphology. It tries to describe the types of toponym and the word formation in tourism sites naming in Ciletuh geopark, Jawa Barat, Indonesia. The method employed in this research is descriptive qualitative method. The data are collected, analyzed, and described related to toponymic and morphological analyses. It is reported that the tourism sites naming in Ciletuh geopark has two different types of toponyms; they are names of natural object or macronyms with hydronyms (14 tourism sites naming) and oronyms (5 tourism sites naming) and names of manmade object or regionyms with comonyms (1 tourism site naming). Related to the word formation, from hydronyms is found blending (3 tourism sites naming), coinage (9 tourism sites naming), and compounding (2 tourism sites naming) while from oronyms is found coinage (3 tourism sites naming) and words from names (2 tourism sites naming). In the names of manmade object or regionyms, there is only one datum that represents comonyms.